Gastroschisis in one twin neonate with extracorporeal liver. Issue 6 (2nd November 2021) - Hudson, Kayla; Birkemeier, Krista L.; Stagg, Hayden; Allen, Steven R.
Abstract: We report a rare case of gastroschisis with extracorporeal liver suspected on late first trimester ultrasound and confirmed with second trimester ultrasound and magnetic resonance imaging in one fetus in a twin pregnancy. Liver herniation is common in omphalocele, a membrane-covered abdominal wall defect associated with other congenital anomalies. However, it is highly uncommon in gastroschisis, an uncovered abdominal wall defect aside of the cord insertion. Presence of liver herniation complicates prenatal differentiation between omphalocele and gastroschisis. The twins were born at 31 weeks' gestation due to preterm labor. The baby was treated with a silo device, followed by biologic mesh and a wound vac with instillation of fluid to prevent desiccation. Ultimately, the baby died of sepsis, with multiorgan failure and polymicrobial infection.